Metabolomic and transcriptomic analyses of the flavonoid biosynthetic pathway in blueberry (Vaccinium spp.) - Li, Yinping; Li, Haifei; Wang, Shiyao; Li, Jing; Bacha, Syed Asim Shah; Xu, Guofeng; Li, Jing (Frontiers in Plant Science, 2023)
As a highly economic small fruit crop, blueberry is enjoyed by most people because of its color, taste, and rich nutrition. To better study the coloring mechanism of blueberry during ripening, integrative analysis of the metabolome and transcriptome profiles was performed in 3 blueberry varieties at 3 developmental stages. First, we analyzed 41 flavonoid metabolites closely related to coloring in blueberry samples and found that the most differential metabolites in the ripening processes of blueberry were delphinidin-3-O-arabinoside (dpara), peonidin-3-O-glucoside (pnglu), and delphinidin-3-O-galactoside (dpgal), while the most differential metabolites among different varieties were flavonols. Second, to obtain more accurate and comprehensive transcripts of blueberry during the developmental stages, we combined PacBio and Illumina sequencing technology to obtain the transcriptome of the blueberry variety Misty for the first time. Finally, using gene coexpression network analysis, the darkviolet and bisque4 modules related to flavonoid synthesis were determined, the key genes related to two flavonoid 3’, 5’-hydroxylase (F3'5'H) genes in the darkviolet module and one bHLH transcription factor in the bisque4 module were predicted. Our results provide valuable information on the molecular mechanism of flavonoid metabolites and flavonoid synthesis pathways in blueberries.